Model Influence Contextual Teaching And Learning Regarding the Reasoning Ability of Class VIII Students at Fatumfaun State Middle School on SPLDV Material - Timutang, Moses; Siahaan, Meiva M. Lestari; Mone, Ferdinandus (MATH-EDU: Jurnal Ilmu Pendidikan Matematika, 2025)
The aim of this research is to determine the effect of the Contextual Teaching and Learning model on the reasoning abilities of class VIII students at SMP Negeri Fatumfaun. The type of research used in this research is quasi experimental with a pretest-posttest control group design. The subjects in this research were students in classes VIII B and VIII C of Fatumfaun State Middle School for the 2023/2024 academic year, totaling 30 students. The research data obtained used research instruments in the form of mathematical reasoning ability test instruments on SPLDV material in the form of 2 essays. Reasoning ability score data was analyzed using due diligence and comparison tests. The results of the research show that there is an influence of the CTL learning model on students' reasoning abilities, this is shown by: 1 the value of the reasoning abilities of students who take part in learning with CTL exceeds the KKM value seen from the test results, namely , 2  the reasoning ability scores of students who took part in learning with the CTL model were better than students who took part in learning with the conventional model, seen from the results of the  test